Pengaruh Pendapatan Terhadap Permintaan Properti Komersial dan Keputusan Investasi di Kota Semarang - Valdin Lazuardi Abu Bakar; Setyo Pantawis (ECONBANK: Journal of Economics and Banking, 2020)
This study aims to obtain empirical evidence of the effect of income on property demand in Semarang City and the effect of income on property investment decisions in Semarang City. The population used in this study are all residents of Semarang City who purchase commercial properties for future investment purposes. A sample of 97 people was taken by purposive sampling technique. The data collection method used a questionnaire. Simple linear regression analysis has been used to analyze the data in this study. The results prove that the income level has a positive and significant effect on property demand and investment decisions in the city of Semarang. Perceptions of public investment decisions in the city of Semarang are quite high but they still consider their instincts, they have not considered the risks and returns on their investments